2013
DOI: 10.1523/jneurosci.5582-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Linked Kinase Regulates Process Extension in Oligodendrocytes via Control of Actin Cytoskeletal Dynamics

Abstract: Integrin-linked kinase (ILK) is a major structural adaptor protein governing signaling complex formation and cytoskeletal dynamics. Here, through the use of conditional knock-out mice, we demonstrate a requirement for ILK in oligodendrocyte differentiation and axonal myelination in vivo. In conjunction, ILK-deficient primary oligodendrocytes are defined by a failure in process extension and an inability to form myelin membrane upon axonal contact. Surprisingly, phosphorylation of the canonical downstream targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 42 publications
1
43
0
1
Order By: Relevance
“…Control of F-actin assembly is known to play an essential role in OL differentiation and initiation of myelination (O'Meara et al, 2013;Zuchero et al, 2015) but the details of the molecular network that links actin dynamics to function in OLs are not fully characterized. With this in mind, we chose to study the recently identified multifunctional actin assembly factor Jmy, which came up in our RNA-Seq screening as an mRNA that is asymmetrically distributed in OPCs during initial extension of membrane protrusions (Figure 1c (Bhat & Zhang, 1996).…”
Section: Jmy Is Expressed In Oligodendrocytes and Upregulated Durinmentioning
confidence: 99%
See 1 more Smart Citation
“…Control of F-actin assembly is known to play an essential role in OL differentiation and initiation of myelination (O'Meara et al, 2013;Zuchero et al, 2015) but the details of the molecular network that links actin dynamics to function in OLs are not fully characterized. With this in mind, we chose to study the recently identified multifunctional actin assembly factor Jmy, which came up in our RNA-Seq screening as an mRNA that is asymmetrically distributed in OPCs during initial extension of membrane protrusions (Figure 1c (Bhat & Zhang, 1996).…”
Section: Jmy Is Expressed In Oligodendrocytes and Upregulated Durinmentioning
confidence: 99%
“…Among the most heavily regulated genes, aside from those encoding myelin proteins, are ones involved in cell cycle and motility, adhesion, and cytoskeletal remodeling. It is likely that different actin regulators have distinct roles in myelination: WASP-family verprolin-homologous protein (WAVE) and integrin-linked kinase (ILK) regulate OL differentiation and axon ensheathment (Kim et al, 2006;O'Meara et al, 2013), while the Arp2/ 3 complex, a major actin nucleator, is required for initiation of myelination in vivo (Zuchero et al, 2015), and Rho GTPases Cdc42 and Rac1 regulate myelin sheath formation (Thurnherr et al, 2006). It has been shown that myelin basic protein (MBP) triggers actin depolymerization by promoting the release of actin disassembly proteins (Zuchero et al, 2015).…”
mentioning
confidence: 99%
“…These estimates assume glucose diffusion to the middle of an internode quickly (see Figure 2); rat internodes average 240 μm (Ransom et al, 1991) while internode lengths in mouse ON average 110 μm (O'Meara et al, 2013). This internode length suggests glucose will readily diffuse; however, the predicted ATP shortfall in axons below 0.8 μm in diameter indicates a potential vulnerability of small axons.…”
Section: Energy In Axonsmentioning
confidence: 99%
“…In cell culture, loxP‐flanked genes can be excised by adding cell‐permeable Cre recombinase to the media (O'Meara et al . ). RT‐PCR showed that 50 nM Cre recombinase significantly decreased the mRNA level of Camk2b in mature OL cultures at 24 h (Fig.…”
Section: Resultsmentioning
confidence: 97%